1993
DOI: 10.1007/bf01957225
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent wheezing in children with respiratory syncytial virus (RSV) bronchiolitis in Qatar

Abstract: Records of 70 infants admitted to Hamad General Hospital with RSV bronchiolitis and a similar number of controls were retrospectively reviewed. Two years after admission, 44% of the infants with RSV bronchiolitis developed recurrent wheezing compared with only 12.9% of controls (P = 0.001). A family history of atopy appeared not to be a significant predisposing factor for the occurrence of recurrent wheezing in post RSV bronchiolitis patients. These results are similar to those from similar studies in industri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0
1

Year Published

2002
2002
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 15 publications
(7 reference statements)
2
19
0
1
Order By: Relevance
“…This was followed by smoking during pregnancy for wheezing and recurrent wheezing, and by male sex for wheezing. In this regard, the present study confirms the result of many others [4][5][6][7][8][9][10][11][12][13]. Likewise, smoking in the family [6,8,9], and in particular smoking during pregnancy [24], were previously identified as risk factors for wheezing.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This was followed by smoking during pregnancy for wheezing and recurrent wheezing, and by male sex for wheezing. In this regard, the present study confirms the result of many others [4][5][6][7][8][9][10][11][12][13]. Likewise, smoking in the family [6,8,9], and in particular smoking during pregnancy [24], were previously identified as risk factors for wheezing.…”
Section: Discussionsupporting
confidence: 91%
“…Acute respiratory failure associated with severe bronchospasm, hypoxia, and carbon dioxide retention necessitate hospitalisation of a fraction of y1-2% of RSV-infected children [3]. A close link between RSVinduced bronchiolitis and development of asthma has been identified in several studies [4][5][6][7][8][9][10][11][12][13][14]. However, there are conflicting results concerning an association between RSV bronchiolitis and allergic sensitisation.…”
mentioning
confidence: 99%
“…51,54,60 During 24 months of follow-up, Osundwa et al found that this outcome was significantly higher in RSV-infected children than in controls (44% versus 13%), and that a family history of atopia did not increase the child's susceptibility. 54 Weber's study, with a 19 -33 month follow-up period, showed a higher incidence of wheezing in children with RSV, with a relative risk (RR) of 7.33, and a progressive reduction of the differences between cases and controls with increasing follow-up time. 60 Finally, Fjaerli observed a higher proportion of wheezing diagnosed in children with RSV infection than in controls (48% versus 14%), although there were no differences between RSV bronchiolitis and that caused by other viruses.…”
Section: Resultsmentioning
confidence: 99%
“…51 With regard to methodologic quality, Osundwa's work had important methodologic flaws such as incorrect statistical analysis and failure to adjust for confounding factors, which could represent confounding bias in the interpretation of the results. 54 Weber's study was a prospective follow-up of 3 cohorts (a) children hospitalized with RSV infection (cases); (b) children with no history of hospital admission due to RSV during the epidemic period (control 1); and (c) children born after the epidemic period (control 2). This study has important methodologic limitations, with both major flaws (definition of diagnostic criteria, RSV not excluded in the control group, lack of baseline measures of prognostic factors, and failure to adjust for confounding factors) and minor flaws (incomplete description of inclusion criteria and incorrect analysis of losses to follow-up), which limit the validity of the results.…”
Section: Resultsmentioning
confidence: 99%
“…After RSV-infection associated lower respiratory tract illness (including bronchiolitis and/or pneumonia) requiring hospitalization in infancy, the later occurrence of recurrent wheezing has been 40-44% in toddlers and preschoolers [25][26][27]141,143,[149][150][151] and the prevalence of school-age asthma 5-28% [141,143,150,151].…”
Section: Long-term Outcome Of Early Childhood Wheezing Requiring Hospmentioning
confidence: 99%